Descriptive Case Study on Awareness and Perception of the Importance of Tech Business Incubator (CSJM Innovation Foundation) and NEP 2020 in HEI: Innovation and Start Up Ecosystem in University - KAISTHA, SHILPA DESHPANDE; Tripathi, Anil Kumar (IJRDO- Journal of Educational Research, 2025)
In the dynamic landscape of entrepreneurship and innovation, understanding stakeholders' awareness, perspectives, and expectations is pivotal for cultivating robust entrepreneurial ecosystems. This study aims to explore these aspects, focusing on stakeholders' familiarity with National Education Policy 2020, Government of India initiatives, perceptions of technology business incubators, and interest in pursuing entrepreneurship as a career. Employing a descriptive case study approach, data was collected from diverse stakeholders across various demographics and viewpoints in Chhatrapati Shahu Ji Maharaj University Kanpur, a State Government Public University and tech business incubator “CSJM Innovation Foundation” of Uttar Pradesh through survey questionnaire. The study focused on specific instances within entrepreneurship ecosystems, business incubators, to gather comprehensive insights through result tabulation and statistical analysis. The findings reveal a notable level of awareness among stakeholders regarding policy initiatives aimed at fostering entrepreneurship and innovation, particularly those delineated in the NEP 2020. Perceptions of technology business incubators underscore the significance of mentorship, networking, and access to resources for Start Up success. Moreover, stakeholders demonstrate a discernible interest in pursuing entrepreneurship as a career path, reflecting a burgeoning entrepreneurial mindset and acknowledgment of associated opportunities. The study underscores the importance of informed policy-making, supportive initiatives, and collaborative endeavours in nurturing dynamic entrepreneurial ecosystems and driving economic growth. Through a nuanced understanding of stakeholders' perspectives within specific entrepreneurial contexts, informed interventions can be designed to empower budding entrepreneurs and foster innovation for enduring societal impact.